Trainee welfare: a New Zealand perspective. (June 2019) - Davison, Lorraine; Amer, Huma; Krishnan, Jamuna; Seale, Elisha; Young, Kirsten; Romans, Sarah
Objective: To explore key sources of stress experienced during training by psychiatry registrars and identify which coping strategies they found helpful or unhelpful. Method: We used three data sources: a) 'stress' vignettes written by Stage 3 trainees; b) minutes of regular registrar meetings; c) focus groups. We analysed these using abbreviated grounded theory, generating themes. Results: The main sources of stress during training were disempowerment, adverse events, difficult supervision and cultural perspectives. Other themes included difficulties in after-hours work, and organisational issues. Stressors may differ in impact according to training stage. Peer support and a good supervisory relationship reduced stress. Conversely, a poor supervisory relationship compounded stress. Trainees were motivated to address modifiable problems. Conclusions: A variety of stressors influence training at all stages. Trainees, the College and employers each have a role in promoting trainee welfare. Interlinking cultural dimensions are not currently addressed in the training curriculum and require attention. A good supervisory relationship can buffer many stressors for trainees.